Studies of sleep and seasonal variations in patients with chronic musculoskeletal pain - Abeler, Karin (UiT The Arctic University of Norway, 2021)
Background/aims: Chronic pain is a major health problem, and contributing factors include poor sleep and mental distress. In the subarctic city of Tromsø, clinical impression also suggests worse pain in winter. We aimed to examine whether sleep in patients with chronic musculoskeletal pain differs from pain-free controls, and how psychological processes are related to sleep in these groups. We also examined day-to-day associations between sleep and pain as well as seasonal variations in symptoms. Methods: We assessed self-reports of pain, sleep quality, insomnia, mental distress, and pain catastrophizing, and recorded 1 week of actigraphy and 1 night of home polysomnography (PSG) in patients and controls. Patients were examined both during summer and winter. Results: Group differences indicating worse sleep in patients than in controls were large in sleep quality and insomnia, and small to medium in actigraphy and PSG measures. Mental distress was strongly related to more severe insomnia symptoms and reduced sleep quality in both groups and explained group differences in these measures. Pain catastrophizing was associated with less slow-wave sleep (SWS), and thus potentially less restorative sleep, in patients only. A weak reciprocal association between daytime pain and sleep quality was observed. Finally, patients reported slightly more pain and experienced delayed sleep timing in summer compared to winter. Conclusion: Mental distress was related to worse self-reported sleep quality and insomnia, whereas pain catastrophizing was related to less SWS. In a clinical setting, sleep complaints may therefore be best addressed in a broader context including affective and cognitive functions. The daily reciprocal associations between sleep and pain, and seasonal variations in pain, sleep, and mental distress were minor. However, sleep timing was significantly delayed in summer and may be a target for circadian adjustment in some patients.